3D kinematics of high-z galaxies as seen through the gravitational telescope - Lemoine-Busserolle, M; Sánchez, S; Kissler-Patig, M; Pelló, R; Kneib, J; Bunker, A; Contini, T (2007)
The study of the physical properties of high-redshift galaxies has become one of the major goals of extragalactic astronomy. In particular the massassembly histories of galaxies have been the focus of many studies at redshifts 1 to 3. In the purpose of probing the dynamics of intermediate and high-redshift galaxies, we have designed a research program to carry out a near-infrared spectroscopic follow up of spatially resolved distant galaxies. Here, we present the results for A370-A5 (z=1.341), an arc behind the lens cluster Abell 370 (z=0.374), observed in the case of science verification programme of SINFONI/VLT. The natural magni fication due to massive galaxy clusters allows to spatially resolve and constrain the dynamics of young star forming galaxies 1 to 3 magnitudes fainter than those selected in blank fields. Thus, the study of lensed galaxies allows to probe a low mass regime of galaxies not accessible in standard observation. In this particular case, we found that the gas distribution and kinematics are consistent with a bipolar outflow with a range of velocities of v ∼ 100km/s. © 2007 Springer-Verlag Berlin Heidelberg.